Socio-Cultural Factors Affecting the Management of Sexual and Gender-Based Violence Against Women in Rural Communities-A Case of Busiu Town Council - Brenda Lunyolo (Uganda Christian University, 2024)
The study aimed to investigate the impact of socio-cultural factors on Sexual and Gender Based Violence (SGBV) against women in Busiu Town Council. Specific objectives included assessing the role of bride price practices, inheritance customs, and the composition of LC courts in perpetuating SGBV. Employing a descriptive case study design, 175 respondents were surveyed, determined by Krejcie & Morgan's mathematical table for a population of 320. The findings indicated a significant correlation between these socio-cultural factors and SGBV. Recommendations emphasized the need for community awareness programs, legal reforms, and support services. The study concluded that addressing these socio-cultural dynamics is crucial in combating SGBV effectively.